EXPERIMENTAL STUDIES OF THE CONCEPT BELLA FIGURA IN THE ITALIAN LINGUISTIC CULTURE - T.S. Medvedeva; M.A. Kashkarova (Многоязычие в образовательном пространстве, 2023)
The paper aims at studying the notional, imaginative and axiological components of the concept Bella figura in Italian linguistic culture. The research is based on the results of the experimental studies’ analysis. The following methods were used: association and receptive experiments, analysis of short essays written by Italian informants, comparative analysis, and the ranking method. Relevance of the research is determined by the need to study culturally specific concepts which demonstrate how the culture of a nation is transmitted through language, and thus contribute to optimization of cross-cultural communication. The results of the studies revealed that the concept Bella figura is an essential element of the Italian linguistic culture, as evidenced by the prominent axiological component of the concept, a wide variety of associations as well as subjective definitions and the images connected with them. The conceptual characteristics that have been revealed at all stages of the experimental studies of the concept are: good impression , pleasant appearance and successful self-presentation . It leads to the conclusion that they are significant for the linguistic consciousness of the informants and thereby for the Italian mentality.